Preferensi Masyarakat Terhadap Sistem Prabayar dan Pascabayar untuk Jaringan Gas Rumah Tangga di Wilayah Cikarang - Faisal Samsuri; Joni Welman Simatupang; Rafael Ryan Putra; Abdul Wahid (Jurnal Serambi Engineering, 2021)
Government, through the Head of the Communication Bureau, Public Information Services and Cooperation, Ministry of Energy and Mineral Resources, conveyed a plan to build household gas networks in more than 50 districts and cities that aim to balance the mix of fossil energy use in society. The prepaid system is a payment system that allows users to enjoy services after making a payment. It aims to limit the service as needed, while the postpaid system allows its users to use the service indefinitely during the time span given by the service provider. Currently, the household gas network is equipped with postpaid meters, but it does not rule out the possibility of a prepaid system being applied if it is able to provide better convenience and comfort. Based on the research we conducted to determine public response of Cikarang society against the payment system, as much as 55% of the total sample studied preferred to use the postpaid system rather than the prepaid system on the household gas network. However, it is possible to use prepaid payment system for household gas networks (respondent's result is 35%) if the supporting facilities are continuously improved and developed for better service in the future.